THU0265 IDENTIFYING COMORBID FIBROMYALGIA IN SYSTEMIC LUPUS ERYTHEMATOSUS USING PATIENT-REPORTED OUTCOMES. (June 2019) - Huang, Frank; O'neill, Sean; Fang, Ray; Nguyen, Matthew; Gibson, Kathryn
Abstract : Background: Fibromyalgia (FM) is disproportionately common in patients with systemic lupus erythematosus (SLE) and difficult to diagnose on a background of classical SLE symptoms [1]. The Multi-Dimensional Health Assessment Questionnaire (MDHAQ) has been shown to be useful to recognise improvement over 2 months in a variety of rheumatic conditions including SLE [2] but has not previously been shown to be useful to alert the clinician to comorbid FM in the latter condition. Conversely, the 2011 FM self-report questionnaire is disease-specific and available for use in clinical and epidemiological studies. Administration of multiple forms may be difficult in a busy clinical setting. Objectives: To identify comorbid FM in patients with SLE using patient-reported outcomes (PROs) from the routinely distributed MDHAQ, in comparison to the 2016 revision of the 2010/2011 FM criteria. Methods: Patients with SLE completed an MDHAQ and the 2011 FM Criteria questionnaire. FM status was assigned using the 2016 revision of the 2010/2011 FM criteria as the gold standard. The MDHAQ features six main PROs: body pain, patient global and fatigue score on a 0-10 visual analogue scale, as well as a functional impact score, self-report joint count and symptom checklist which have a range of 0-10, 0-48 and 0-60 respectively. Composite indices consisting of either two or three of patient pain score 6, self-report joint count 16 and symptom checklist 16 or three of four of the same measures plus a fatigue score 6 have been described previously to provide clues to comorbid FM in other rheumatic diseases [3, 4]. Individual PROs and these composite indices were compared between patients with and without FM by student's unpaired t-test and Area Under the Curve (AUC) analysis. The physician's diagnosis of FM was analysed against the FM criteria using Cohen's kappa. Physicians were blinded to the results of the 2016 FM criteria. Results: 88 patients with SLE were studied, of whom 23 (26%) satisfied FM criteria. Those with FM reported higher scores in all PROs. A patient global of 6 could correctly classify 90% of patients and provided the highest AUC of 0.95, followed by the symptom checklist and body pain. An index of three measures (pain score, self-report joint count and symptom checklist) gave an AUC of 0.90. An index of four measures (additional fatigue criterion) gave an AUC of 0.93. Both indices correctly classified 89% of patients with a cut-off of 2 and 3 respectively. The physician's diagnoses had moderate agreement with the FM criteria (kappa = 0.43). Conclusion: Comorbid FM is prevalent in SLE yet often missed by physicians. In busy clinical settings, composite indices provide useful clues to coexisting FM in SLE, although a simple MDHAQ patient global is quick and potentially just as valuable in this patient group. These findings require further validation in a larger cohort. References: [1] Wolfe F, Petri M, Alarcon GS, Goldman J, Chakravarty EF, Katz RS, et al. Fibromyalgia, systemic lupus erythematosus (SLE), and evaluation of SLE activity. J Rheumatol. 2009;36(1):82-8. [2] Castrejon, I., M.J. Bergman, and T. Pincus, MDHAQ/RAPID3 to recognise improvement over 2 months in usual care of patients with osteoarthritis, systemic lupus erythematosus, spondyloarthropathy, and gout, as well as rheumatoid arthritis. J Clin Rheumatol, 2013. 19(4):p.169-74 [3] Gibson K et al. 2016 MDHAQ as a useful screening tool for fibromyalgia in busy clinical settings Ann Rheum Dis, volume 75, supplement 2, page 88 [4] Schmuckler J, et al. 2018 A simple index based on scores on a multidimensional health assessment questionnaire (MDHAQ) provides information quite similar to ACR criteria for fibromyalgia in routine care Ann Rheum Dis, volume 77, Suppl, page A465 Disclosure of Interests: Frank Huang: None declared, Sean O'Neill: None declared, Ray Fang: None declared, Matthew Nguyen: None declared, Kathryn Gibson Grant/research support from: UCB, Abbvie, Speakers bureau: UCB, Janssen